An updated checklist of the liverworts and hornworts of southern Africa - Phephu, Nonkululo; Witkowski, Ed T.f.; Rooy, Jacques Van; Sim-Sim, Manuela (Phytotaxa, 2025)
This updated checklist of liverworts and hornworts recorded in the Flora of southern Africa (FSA) area is based on herbarium collections, databases, and literature. It comprises 315 species, including 5 subspecies and four varieties, of which 77 are endemic, in 92 genera and 45 families. South Africa has 96% of the liverworts whereas 29%, 11%, 10% and 6% occur in Lesotho, eSwatini, Namibia and Botswana, respectively. The Western Cape Province is the most species-rich region in the entire study area containing 60% of FSA liverwort species. The top three contributors to liverwort species richness in the region are Ricciaceae, with 59 species and 31 endemic species, Lejeuneaceae with 50 species and five endemics, and Fossombroniaceae with 20 species and 16 endemic species. New regional records since the last liverwort checklists of South Africa and southern Africa are provided and literature references are given in the checklist for nomenclatural and taxonomic changes. The quality of the dataset used in this study was affected by taxonomic and sampling biases, namely, Linnaean and Wallacean shortfalls. Among the taxonomic changes incorporated in this checklist are new combinations as well as the validation of previously uncertain records.